Structural characterization and energy performance of novel hybrid PVT solar-panels through 3-D FEM and CFD simulations - Herrando,M; Ramos,A; Zabalza,I; Markides,CN (2017)
Hybrid Photovoltaic-Thermal (PVT) panels generate both power and heat from the same area with overall efficiencies up to 70%. This work assesses the performance of novel hybrid PVT solar panels considering alternative geometries and materials that maximize heat transfer while allowing weight and cost reductions. A three-dimensional (3-D) model previously developed and validated using 3-D Finite-Element and Computational Fluid-Dynamics (FEM and CFD) software is used for this purpose. The most promising configurations and materials for the absorber-exchanger unit of the proposed PVT panel are studied to analyse their energy performance and behaviour in terms of a thermal-stress assessment. Apart from an assessment of the steady-state performance, for the type of solar PVT panels considered, especially those made of polymeric materials, it is important to evaluate the thermal expansion that the collector suffers, so as to verify whether the associated thermal stresses and strains are within the limits that guarantee a proper performance during its lifetime. The most promising PVT panel is then integrated within a Solar Combined Heat and Power (S-CHP) system for power and heating provision to a single-family house located in Zaragoza (Spain), in order to assess its daily energy performance through transient simulations on half-hourly basis. The results show that these novel polymeric PVT panel configurations are a promising alternative to commercial PVT panel designs, achieving an improved thermal performance compared to a reference case (4% higher optical efficiency and 15% lower heat loss coefficient), while suffering lower strains in most of the PVT layers. Furthermore, the novel polycarbonate 3×2 mm flat-box configuration has the potential to cover, on average, around 50% of the total space heating and Domestic Hot Water (DHW) demand and around 87% of the total electricity demand (including lighting, cooling and home appliances).